PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA DALAM MENINGKATKAN JIWA INTRAPRENEURSHIP - Suyatmi, Suyatmi; Pahlevi, Reza Widhar (Journal Competency of Business, 2022)
Intrapreneurship is a strategy for fostering innovation through making better use of the employees of a company. When intrapreneurship goes wrong and is abandoned, it won't just spur innovation; it'll also assist those who have good ideas to help their companies raise money to create more innovative products. Pegawai can become an agent for business change by encouraging intrapreneurship within the company. The purpose of the study is to comprehend the role that expertise and work environment play in fostering intrapreneurship. As a result of the survey's use of 25 indicators for each and every variable, more than 150 respondents from the University of Amikom Yogyakarta responded. The research's findings indicate that it is possible to combine and simultaneously improve one's skills and professional network in order to foster intrapreneurship.